Supportive, interactive staff training may improve outcomes for residents dying in a care home. Issue 2 (1st June 2012) - Lewis-Holmes, E.; Taylor, E.; Pitfield, C.; Morris, J.; Wills, G.; Carson, N.; Jacobs, H.; Livingston, G.
Abstract : Introduction: Dementia is associated with shortened life expectancy. Death may occur unexpectedly without end of life care planned. Most people would prefer to die at home, if possible, rather than in hospital. However, many with advanced dementia lack explicit end of life plans. Aims and Methods: The project aimed to increase the number of residents with dementia (RWD) receiving their end of life care in the way that they and their relatives planned. We trained staff interactively, using case scenarios and encouraging reflection on their work, to enable end of life discussions with relatives. Our evaluation included residents' quality of life (QoL), and measures of staff's job demands. We implemented a training package addressing staff concerns, knowledge and communication skills. In depth interviews were carried out with staff and relatives, and collected QoL measures from 53 relatives of RWD, and retrospectively if their relative died. Staff job demand was measured. Results: Interview analysis showed improvements in end-of-life planning and communication, and QoL improved at RWD's end-of-life. Staff's experience of job demand improved. Conclusion: The intervention improved end-of-life communication, planning and care, as shown by themes in qualitative analysis and QoL measures.